Clinical Efficacy and Safety of Combined House Dust mite Subcutaneous Immunotherapy and Omalizumab in Five Cases of Allergic Rhinitis and Asthma - P.C. Kathuria; Manisha Rai (Indian Journal of Medical Specialities)
Allergen immunotherapy (AIT) is a well-recognized treatment for altering the natural course of respiratory allergy which builds immune tolerance and prevents progression of allergic diseases. In our five cases of house dust mite (HDM)-driven allergic rhinitis and asthma, combined HDM Subcutaneous Immunotherapy (HDM-SCIT) for 2 years with omalizumab for more than 12 months has achieved disease remission in four cases and disease control in one case along with long-term effect for 3 years after discontinuation of AIT. We hypothesize that combining HDM-SCIT and omalizumab is a promising strategy as it is effective, safe, and synergistic having immune-modifying activity in cases of HDM-driven Allergic Rhinitis and Asthma.